The language of radicalization: female internet recruitment to participation in ISIS activities - Windsor, Leah C. (Terrorism and political violence, 2020)
Why do young Muslim women radicalize and undertake high-risk political behaviors, and what factors influence their sociopolitical transformation? The process of radicalization happens because of individual, social, and political dynamics, and is facilitated by the availability of computer-mediated communication. Some young Muslim women keep detailed records of their radicalization process via social media, which we use to understand their sociopolitical transformation. By evaluating their language, we can better understand how their personal, social, and political development unfolds. This paper is a case study examining the words of one young Muslim woman, Aqsa Mahmood, who moved from her home in Scotland to join the ISIS fighters in Syria. Her Tumblr blog provides a linguistic, political, and ideological record of the process of her radicalization. We identify linguistic patterns in her blog posts that can help to develop and reveal a typology of the language of female radicalization.